Adalimumab and Etanercept in the Treatment of Rheumatoid Arthritis and Spondyloarthropathies: Budget Impact Model of Dose Reduction - Alejandro González Álvarez; Manuel Gómez Barrera; Joaquín Borrás Blasco; Emilio José Giner Serret (Journal of Pharmacy and Nutrition Sciences, 2014)
Objective:To assess the financial impact ofspacing out the administration intervals of adalimumab (ADA) and etanercept (ETN) in the treatment of rheumatoid arthritis (RA) and spondyloarthropathies (SAP) in our work setting. Materials and method:A budget impact model (BIM) was developed to estimate the financial impact ofspacing out the usual administration intervals of ADA 40 mg every 2 weeks and ETN 50 mg weekly (scenario A) to ADA 40 mg every 3 weeks and ETN 50 mg every 2 weeks (scenario B), according to the guidelines and recommendations applied to these studies, specifying the target population, the study perspective, the time frame, and analysing the robustness of the study with a threshold univariate sensitivity analysis. Results:A total of 71 patients were included in the study.The application of a BIM showed annual savings for ADA and ETN of €19,784 and €38,271, respectively.The net cost, that is, the savings this entailed for the time frame considered (2 years), amounted to €116,110.The sensitivity analysis performed shows that the BIM estimated for the study period was very robust, as the net result in the different scenarios varied very little, remaining negative in the new scenarios. Conclusions:The BIM developed in the study shows the importance of the role of healthcare professionals in the context of sustainability of the healthcare system, where the model could generate large annual net savings for the different regional healthcare systems.